(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, the role of spirituality and legal sciences in the educational system, modern knowledge skills and modern professional skills, education of young people who have their own independent opinion, awareness of their rights and in the spirit of national and universal values, Law sciences in increasing the legal potential of today’s youth and strengthening knowledge, information about them is given.